Islamic Law Strategy in the Context of National Law: Harmonization and Adaptatio - Ritonga, Raja; Sri Wahyuni; Shofwan Karim; Wendra Yunaldi; Rusydi (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2024)
In Indonesia, Islamic law plays a significant role in various aspects of societal life, despite being within the framework of the national legal system based on positive law. Given the diversity of existing norms, the implementation of Islamic law within the context of national law often presents challenges in terms of integration and harmonization. Therefore, it is important to understand strategies that can be applied to accommodate the values of Islamic law within the plural national legal framework. This article aims to analyze and identify strategies that can be applied to integrate the principles of Islamic law into Indonesia's national legal system. The approach used in this study is qualitative, utilizing literature analysis and doctrinal study of legal texts, both Islamic law and positive law in Indonesia. Additionally, an analysis is conducted on the application of Islamic law in various legal fields in Indonesia, such as family law, religious courts, and criminal law. The findings indicate that the integration of Islamic law into Indonesia's national legal system requires a more contextual and adaptive approach, considering local values and societal diversity. Several strategies that can be implemented include harmonizing Islamic legal norms with positive law, enhancing the understanding of legal pluralism, and adjusting the implementation of Islamic law to align with the principles of social justice in Indonesian society.